Antimicrobial susceptibility of Neisseria gonorrhoeae isolates and treatment of gonorrhoea patients in Ternopil and Dnipropetrovsk regions of Ukraine, 2013–2018. Issue 7 (21st May 2019) - Boiko, Iryna; Golparian, Daniel; Krynytska, Inna; Bezkorovaina, Halyna; Frankenberg, Arkadii; Onuchyna, Margarita; Jacobsson, Susanne; Unemo, Magnus
Abstract : Antimicrobial resistance (AMR) in Neisseria gonorrhoeae is a major public health concern globally. However, recent gonococcal AMR data from Eastern Europe are extremely limited and no AMR data for strains spreading in Ukraine have ever been internationally published. We investigated the AMR of N. gonorrhoeae isolates in two regions of Ukraine (Ternopil 2013–2018, Dnipropetrovsk 2013–2014), and, where information was available, the treatment administered to the corresponding gonorrhoea patients. Determination of minimum inhibitory concentration (MIC) of eight antimicrobials was performed using Etest and resistance breakpoints from the European Committee on Antimicrobial Susceptibility Testing (EUCAST) were applied. Overall, 9.3% of the examined 150 isolates were resistant to ciprofloxacin, 6.0% to tetracycline, 2.0% to azithromycin, and 0.7% to benzylpenicillin. No isolates were resistant to ceftriaxone, cefixime, spectinomycin, or gentamicin. However, one (0.7%) isolate showed a MIC value of 0.125 mg/L for both ceftriaxone and cefixime, i.e., bordering resistance. Eighty‐eight (67.2%) of 131 patients were administered dual therapy (ceftriaxone 1 g plus doxycycline/clarithromycin/azithromycin/ofloxacin) and 22 (16.8%) ceftriaxone 1 g monotherapy. Worryingly, 21 (16.0%) patients received monotherapy with clarithromycin/doxycycline/azithromycin/ofloxacin/benzylpenicillin. In conclusion, the antimicrobial susceptibility of gonococcal strains spreading in Ternopil and Dnipropetrovsk, Ukraine during 2013–2018 was high. Low levels of resistance to ciprofloxacin, tetracycline, azithromycin, and benzylpenicillin were found, but no resistance to the internationally recommended ceftriaxone, cefixime, or spectinomycin. Ceftriaxone 1 g should remain as empiric first‐line treatment, in dual therapy with azithromycin or doxycycline or in monotherapy. Continued and expanded gonococcal AMR surveillance in Ukraine is essential to monitor the susceptibility to particularly extended‐spectrum cephalosporins, azithromycin and doxycycline.